Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil - Waichert, Cecilia; Colombo, Wesley Dondoni; Von Dohlen, Carol D.; Pitts, James P. (Zootaxa, 2018)
Ageniella Banks is the second most diverse genus in the tribe Ageniellini (Pompilidae: Pepsinae) with about 200 valid names. Ageniella is known to be paraphyletic; yet, no revision has been made. Lack of a taxonomic catalogue and of identification keys has further delayed taxonomic studies. Additionally, many of the currently valid names should be treated as synonyms. This present study is the first attempt to organize the species of Ageniella, focusing on the species occurring in Brazil. A total of six subgenera and 40 species of Ageniella occur in Brazil. Of these, 25 species are endemic to Brazil. The new synonyms are proposed for (valid names are first): Alasagenia Banks, 1944 =Lissagenia Banks, 1946, syn. nov.; Ageniella (Alasagenia) erichsoni Banks, 1944 =Priophanes major Banks, 1945, syn. nov.; Ageniella (Ameragenia) zeteki (Banks, 1925) =Priophanes marcida Banks, 1946, syn. nov.; Ageniella (Ameragenia) agitata (Smith, 1873), comb. nov. =Salius (Priocnemis) setaceicornis Fox, 1897, syn. nov.; Ageniella (Ameragenia) sanguinolenta (Smith, 1864) =Agenia ruficeps Smith, 1864, syn. nov.; =Ageniella alternata Banks, 1946, syn. nov.; Ageniella (Priophanes) dolorosa (Banks, 1946), comb. nov. =Priophanes plagosa Banks, 1946, syn. nov.; Ageniella (Ameragenia) fabricii (Banks, 1944) =Ameragenia notabilis Banks, 1946, syn. nov. A new combination is proposed for: Ageniella (Alasagenia) cursor (Smith, 1873), comb. nov. (from Agenia Schiødte); Ageniella (Ameragenia) clypeata (Fox, 1897), comb. nov. (from Salius Fabricius), Ageniella (Ameragenia) rutila (Fox, 1897), comb. nov. (from Salius), Ageniella (Priophanes) tegularis (Fox, 1897), comb. nov. (from Salius), Ageniella (Priophanes) rufitarsis (Fox, 1897), comb. nov. (from Salius), Ageniella (Ameragenia) citricornis (Fox, 1897), comb. nov. (from Salius), Ageniella (Ameragenia) serrula (Fox, 1897), comb. nov. (from Salius), Ageniella (Priophanes) cingulata (Fox, 1897), comb. nov. (from Agenia). A new name Ageniella (Ameragenia) banksii Waichert, nom. nov. is proposed for Ameragenia festina Banks, 1946, secondary homonym of Ageniella festina Banks, 1917, and Ageniella (Priophanes) otiosa is reinstate, stat. resurr.